Penerapan Metode Proyeksi Citra pada Citra Kamera 360 Derajat untuk Mengukur UGR - Abiyyu Fathin Derian; Faridah Faridah; Rizki Armanto Mangkuto (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2019)
The quality of lighting in a room will affect visual comfort. It is determined by light beam that hits observer’s eyes generating a specific response. Meanwhile, the indicator that represents visual comfort is glare, especially discomfort glare. Glare index in a room, one of them, is stated by Unified Glare Rating (UGR) value affected by the ratio of glare source’s luminance and background in a specific solid angle and position between observer and luminaire. As a result, it is needed to conduct an assessment to know glare potency in a room. The popular method measuring UGR is by analyzing pixel value from High Dynamic Range (HDR) image captured by 180-degree camera. At the same time, the implementation of 360-degree camera in assessing photometry has also been developed. However, the implementation is not been applied to measure glareyet. Therefore, this paper is aimed to implement 360-degree camera determining UGR value of HDR image. It is conducted by comparing the UGR value to 180-degree camera image. The result shows the significant irrelevance of both cameras. Statistical analysis on Lmean and Lstd found that the coefficient of determination is less than one and Root Mean Square Error(RMSE) is bigger than 0.1, while F-test and T-test results are less than 0.05. The value of Coefficient Variation ( CV) 180-degree camera is bigger than 360-degree camera which stated the data of luminance value is more spread out. It shows that the use of 360-degree camera with per-pixel analysis on HDR image to measure glare is not appropriate.